Analysis of Gamification Implementation on the Marketplace: Testing the Effect of User Feedback on the Marketplace Using Self Determination Theory and Technology Acceptance Models - Fitriana, Risa Naili; Abidin, Zaenal (Journal of Advances in Information Systems and Technology, 2023)
The development of the marketplace produces a variety of features to attract users to engage with content. Gamification is one of the marketing tools that is currently trending and many are already using it, one of which is the marketplace. The purpose of this study is to examine the impact of the application of gamification in the marketplace on the effect of marketplace user feedback. The marketplaces used in this research are Shopee and Tokopedia. This study uses a quantitative method using the Self Determination Theory model combined with the Technology Acceptance Model. The results of the questionnaire data collection from 252 data contained 208 valid data. The results of data processing using SmartPLS produced four indicators with values ​​below 0.7 including A1, A5, PEU4, and C5, so modifications were made to the research model. Based on the results of data processing, all of the hypotheses of this study were significant or accepted as many as 9 hypotheses. The results show that user attitudes greatly determine the sustainability of users towards the use of the marketplace and the pleasure of users when playing games on the marketplace is one of the main factors in determining user attitudes towards the marketplace. This study provides recommendations that related parties in making game features on the marketplace focus more on user enjoyment when playing games, because user pleasure is one of the main factors in determining user attitudes and user attitudes towards game features on the marketplace encourage users' intentions to use the marketplace.